ANTIBACTERIAL ACTIVITY TESTING OF HAND SANITIZER GEL EXTRACT OF CORIANDER (CORIANDRUM SATIVUM L.) SEEDS AGAINST STAPHYLOCOCCUS AUREUS - Ariyanthini, Kadek Sutri; Angelina, Elisabeth; Permana, Kadek Nanda Banyu; Thelmalina, Fiorenza Jocelyn; Prasetia, I Gusti Ngurah Jemmy Anton (Journal Pharmaceutical Science and Application; Vol 3 No 2 (2021): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2021.v03.i02.p06, 2021)
Background: Staphylococcus aureus is a bacterium that causes bacteremia in COVID-19 pneumonitis patients. S. aureus is responsible for 80% of suppurative disease, with the skin surface as its natural habitat. So, maintaining hand hygiene during a pandemic is very important. Currently, people prefer the use of practical hand sanitizers. Most hand sanitizers contain alcohol, which has the potential to irritate. Thus, the active substance of coriander seed extract is used as a substitute for alcohol. Objective: To determine the characteristics of the gel and the concentration of coriander seed extract which gave antibacterial effect against S. aureus . Methods: The resulting hand sanitizer gel was then tested for characteristics and antibacterial activity against Staphylococcus aureus by the Kirby-Bauer diffusion method and analyzed by the One Way Anova-LSD method. Result: The results showed that preparations with concentrations of F1(2%), F2(4%), and F3(6%) respectively had inhibition zones of 1.00 ± 0.82 mm, 5.00 ± 0.41 mm, and 5 .25 ± 1.26 mm. Conclusion: Formulas 2 and 3 were able to inhibit the growth of S. aureus with moderate inhibition category. The hand sanitizer gel meets the requirements for organoleptic tests, pH, homogeneity, dispersibility, and adhesion. However, the viscosity of the preparation did not meet the requirements. Keywords: Coriander Seed Extract, Gel Hand Sanitizer, Antibacterial